Implementation of Instructional Design to Enhance the Creativity of Islamic Religious Education Teachers at SMP Negeri 1 Hinai - Syarifah Alwiyah; Syarifah Rahmah; Aulia Rahmat (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The research entitled Implementation of Learning Design in Improving the Creativity of Islamic Religious Education Teachers at SMPN 1 Hinai aims to: (1) describe how the implementation of learning design can improve the creativity of Islamic Religious Education teachers at SMPN 1 Hinai; and (2) identify the factors of Islamic Religious Education teachers' creativity in developing learning design. This research is a qualitative study with a case study approach. Data sources consist of Islamic Religious Education teachers, curriculum representatives, and two students. Data collection techniques include observation, interviews, and documentation. Data analysis uses three stages: data condensation, data presentation, and verification. The results of the study indicate that the implementation of learning design can improve the creativity of Islamic Religious Education teachers at SMPN 1 Hinai through several aspects, namely: (a) systematic organization of materials through the preparation of Teaching Modules, Semester Programs, and Annual Programs; (b) effective communication developed through collaboration in regional languages when explaining materials; (c) teacher mastery and enthusiasm for the subject matter; (d) a positive attitude without prejudice towards students. In addition, the creativity of Islamic Religious Education teachers in developing learning designs at SMPN 1 Hinai is influenced by several factors, namely: (a) cooperation between teachers and leaders; (b) giving awards and encouragement by the principal; (c) treatment that does not differentiate employee status; (d) giving teachers trust to explore creativity without coercion; and (e) teacher involvement in the preparation of school policies.